(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
This paper analyzes Shukritdin Pakhrutdinov’s book «Taraqqiyotga tahdid: nazariya va amaliyot» (Threats to Development: Theory and Practice) in the context of contemporary global political processes. The book represents a comprehensive philosophical and political science study of the nature of threats to societal and state development, emphasizing their systemic interconnection with social, economic, political, and spiritual dimensions. The author treats threats not as random crises but as objective phenomena requiring a comprehensive and preventive approach. Special attention is given to the critique of the “struggle of opposites” concept in politics and the development of a framework based on proportionality, complementarity, and consensus to achieve sustainable development. The study examines economic, informational, ideological, and spiritual threats, demonstrating their relevance through contemporary local and global conflicts, sanctions, economic instability, and globalization processes. The author proposes strategies for early threat detection, economic diversification, social protection, and strengthening the spiritual and cultural potential of society. The analysis shows that Pakhrutdinov’s ideas are of universal significance and can guide state and international strategies aimed at crisis prevention and long-term stability.